Juvenile Delinquency and the Limits of Western Influence, 1850-2000
X, 280 p.
Keywords: This volume brings together a wide range of case studies from across the globe, written by some of the leading scholars in the field, to explore the complex ways in which historical understandings of childhood and juvenile delinquency have been constructed in a global context.